Additions of Thiols to 7-Vinyl-7-deazaadenine Nucleosides and Nucleotides. Synthesis of Hydrophobic Derivatives of 2'-Deoxyadenosine, dATP and DNA - Slavíčková, Michaela; Pohl, Radek; Hocek, Michal (The Journal of organic chemistry, 2016)
Additions of alkyl- or arylthiols to 7-vinyl-7-deaza-2'-deoxyadenosine gave a series of 7-[2-(alkyl- or arylsulfanyl)ethyl]-7-deaza-2'-deoxyadenosines in 45-85% yields. The nucleosides were converted to 5'-O-mono-(dASRMP) or triphosphates (dASRTP) by phosphorylation. The modified triphosphates were also prepared by thiol addition to 7-vinyl-7-deaza-dATP. The triphosphates dASRTP were good substrates for DNA polymerases useful in the enzymatic synthesis of base-modified oligonucleotides (ONs) or DNA containing flexibly linked hydrophobic substituents in the major groove. Primer extension was used for the synthesis of ONs with one or several modifications, PCR was used for the synthesis of heavily modified DNA, whereas terminal deoxynucleotidyl transferase was used for a single-nucleotide labeling of the 3'-end.
Keywords: Deoxyadenosines; Electrophoresis, Polyacrylamide Gel; Base Sequence; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; polymerázová řetězová reakce; Polymerase Chain Reaction; Nucleosides; DNA; Vinyl Compounds; sulfhydrylové sloučeniny; deoxyadeninnukleotidy; nukleosidy; deoxyadenosiny; magnetická rezonanční spektroskopie; Deoxyadenine Nucleotides; hydrofobní a hydrofilní interakce; Sulfhydryl Compounds; sekvence nukleotidů; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Magnetic Resonance Spectroscopy; elektroforéza v polyakrylamidovém gelu; vinylové sloučeniny; Hydrophobic and Hydrophilic Interactions